Implantación del sistema de contabilidad comercial por cuenta múltiple en “La Casa del Perno” de la ciudad de Loja, periodo enero a marzo del 2014 - Espinosa Villacis, Jorge Washington (2015)
The present work of the Thesis namedi “Implantation of Commercial Accounting System for Multiple Account in “The House of the Bolt” of Loja City, period January a March 2014”, it is a business house applied to several products of hardware shop, it brought about with the purpose to contribute as a good guide to control profits, and expenses with high efficiency. The objectives of this work were carried out with the organization of the documents these papers were used to elaborate the reports for the transactions, the design of auxiliares records to take care of the mechanisms that the hardware shop presents according to different activities that it brings about with out difficulty after the organization of everything it was elaborated the accounting period to get the financial conditions. To finish this work it has formulated conclusions and recommedations and it is important to out that the hardware shop does not have a good accounting system to obtain an excellent economical and financial position, therefore it is recommended to apply and accounting system in order to get good results and convenient information to take on a responsibility